Loss-of-function variants in ADCY3 increase risk of obesity and type 2 diabetes. (February 2018) - Grarup, Niels; Moltke, Ida; Andersen, Mette; Dalby, Maria; Vitting-Seerup, Kristoffer; Kern, Timo; Mahendran, Yuvaraj; Jørsboe, Emil; Larsen, Christina; Dahl-Petersen, Inger; Gilly, Arthur; Suveges, Daniel; et al.
Abstract We have identified a variant inADCY3 (encoding adenylate cyclase 3) associated with markedly increased risk of obesity and type 2 diabetes in the Greenlandic population. The variant disrupts a splice acceptor site, and carriers have decreasedADCY3 RNA expression. Additionally, we observe an enrichment of rareADCY3 loss-of-function variants among individuals with type 2 diabetes in trans-ancestry cohorts. These findings provide new information on disease etiology relevant for future treatment strategies. Individuals from a Greenlandic Inuit population with homozygous loss-of-function variants inADCY3 (adenylate cyclase 3) have increased risk for obesity and type 2 diabetes. Carriers of rareADCY3 variants in trans-ancestry populations also show increased association with type 2 diabetes.